Pelestarian Benda Cagar Budaya dan Pemanfaatannya bagi Pembangunan Bangsa - Tjandrasasmita, Uka (Lajnah Pentashihan Mushaf Al-Qur'an, 2010)
This paper examines cultural heritage objects and their use for the development of the nation. Its subject is the National Ordinance (Undang-Undang) No.5 1992 concerning Cultural Heritage Objects.Ã‚Â Differing forms of regulations contained in this law can also be found in other countriesÃ¢â‚¬â„¢ statutes. Cultural heritage objects are not pre-served merely as a formality, but also have a social function and can be used for national development.Ã‚Â Cultural heritage objects must be unconditionally preserved, through both legal statutes and grant funding for their conservation,Ã‚Â in order that they are guarded from natural and human destruction.